Symptoms and Character Traits in Patients Selected for Long-term Psychodynamic Psychotherapy - Wilczek, Alexander (American Psychiatric Press, Inc, 1998)
In this naturalistic study of 55 outpatients selected for long-term psychodynamic psychotherapy, two Swedish assessment instruments are presented (the Karolinska Psychodynamic Profile and the Karolinska Scales of Personality), and the significance of psychodynamic criteria for the selection of patients is discussed. Thirty patients (55%) fulfilled criteria for a DSM-III-R diagnosis. The most prominent psychodynamically defined character pathology was found in the areas of coping with aggressive affects; dependency and separation; frustration tolerance; and impulse control. Some psychodynamically defined character traits, particularly poor frustration tolerance, were related to symptomatic suffering.